2005
DOI: 10.1111/j.1528-1167.2005.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Central‐type Benzodiazepine Receptors and Epileptogenesis: Basic Mechanisms and Clinical Validity

Abstract: Methods: We examined interictal 123 I-IMZ SPECT in patients with mesial temporal lobe epilepsy (MTLE; n = 19) with hippocampal sclerosis and neocortical epilepsy with focal cortical dysplasia (NE-CD; n = 18), and compared those with magnetic resonance imaging (MRI) and 123 I-IMP SPECT (for regional cerebral blood flow). We also investigated in vitro autoradiography with 123 I-IMZ at various time courses in the intraamygdala kainate, amygdala kindling, and in-utero irradiation models.Results: In MTLE patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…Studies in mesial TLE showed decreased binding that correlated with decreased neuronal density in the hippocampus and dentate gyrus. Similar changes were present in neocortical dysplasia, even in the absence of structural MRI lesions or SPECT studies evaluating cerebral blood flow [108,109]. Among patients who had severe TBI, hypoperfusion in the temporal lobes 1 year after trauma, as measured with 99m Tc hexamethyl-propyleneamine-oxime, correlated highly with the development of PTE [110].…”
Section: Single Photon Emission Computed Tomographysupporting
confidence: 49%
“…Studies in mesial TLE showed decreased binding that correlated with decreased neuronal density in the hippocampus and dentate gyrus. Similar changes were present in neocortical dysplasia, even in the absence of structural MRI lesions or SPECT studies evaluating cerebral blood flow [108,109]. Among patients who had severe TBI, hypoperfusion in the temporal lobes 1 year after trauma, as measured with 99m Tc hexamethyl-propyleneamine-oxime, correlated highly with the development of PTE [110].…”
Section: Single Photon Emission Computed Tomographysupporting
confidence: 49%
“…It has been reported that a low IMZ uptake level correlates with decreased neuronal density in epilepsy patients [7, 9]; and IMZ has already been used for epilepsy diagnosis in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…49 It has not yet been proven that either of the available benzodiazepine ligands is more accurate for delineation of the seizure focus than the functional imaging techniques already in clinical use (as detailed above). 48,[50][51][52] There are promising indications. When hippocampal sclerosis was present, the area of abnormality was often larger on FDG-PET than on FMZ-PET, which more closely matched the epileptogenic zone as determined by intracranial EEG.…”
Section: Benzodiazepine-gaba a Receptormentioning
confidence: 97%